2010
DOI: 10.1007/s11910-010-0103-9
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Pediatric Brain Tumors

Abstract: Brain tumors are the most common childhood solid malignancy and the leading cause of cancer-related death in children. Medulloblastoma, ependymoma, supratentorial primitive neuroectodermal tumors, and pilocytic astrocytoma are the most prevalent types, all of which are clinically, histologically, and genetically heterogeneous. Despite an incomplete molecular understanding of these tumors, we have made significant headway in the past 5 years in identifying and classifying important genetic alterations and pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 56 publications
0
47
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Current therapy for posterior fossa ependymoma in children is aggressive surgical resection followed by involved-field radiation, resulting in 7-year event free-survival of 65%. 12,15 Despite the high mortality rate, trials of cytotoxic chemotherapy have failed to reveal a clear survival benefit for chemotherapy over surgery and radiation alone, although definitive pediatric randomized trials of maintenance chemotherapy are still recruiting through cooperative groups (ClinicalTrials.gov identifiers: NCT01096368 and NCT02265770).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Current therapy for posterior fossa ependymoma in children is aggressive surgical resection followed by involved-field radiation, resulting in 7-year event free-survival of 65%. 12,15 Despite the high mortality rate, trials of cytotoxic chemotherapy have failed to reveal a clear survival benefit for chemotherapy over surgery and radiation alone, although definitive pediatric randomized trials of maintenance chemotherapy are still recruiting through cooperative groups (ClinicalTrials.gov identifiers: NCT01096368 and NCT02265770).…”
Section: Introductionmentioning
confidence: 99%
“…33,125 For example, epigenome-wide studies emerged as large-scale screenings of epigenetic alterations in the genome that allow the identification of epigenetic signatures or candidate genes that are ultimately silenced in cancer. However, it remains a challenge to treat these tumors because the effects of radiation and chemotherapy can be particularly hazardous for the developing brain and may cause other tumorigenic events in rapidly dividing normal cell populations.…”
mentioning
confidence: 99%
“…• While even the most malignant gliomas rarely spread outside the CNS, the subarachnoid space allows tumor diffusion to distant regions along the neural axis, in addition to local infiltration [9,14].…”
Section: Incidence Of Brain Tumors and Overviewmentioning
confidence: 99%
“…However, there were some points which were not substantiated with sufficient data and posed problems in terms of repeatability within this system; 2007 classification was prepared by more than 70 specialists, in light of the literature data obtained until that time. The studies conducted on brain tumors in the last two decades unveiled the genetic basis of tumorogenesis and demonstrated that it is possible to contribute to the classification of these tumors [5][6][7][8][9][10][11]. In fact, the Haarlem meeting held in 2014 paved the way for a major revision in the 2007 CNS classification of incompatible molecular findings in the diagnosis of brain tumors [12]; 2016 CNS WHO classification was prepared with the contribution of 117 participants from 20 countries and 35 neuropathologists and neuro-oncologists from 10 countries who elaborated on topics of debate [13].…”
Section: Introductionmentioning
confidence: 99%